Analisis Perbandingan Kinerja Keuangan Daerah Pada Pemerintah Kota Jambi Dan Pemerintah Kabupaten Tebo Tahun 2018-2022 - Restiana Restiana; As’ad Isma; Ahmad Syukron Prasaja (Ebisnis Manajemen, 2024)
Regional government financial performance is a measure used to ensure the region's ability to implement financial implementation regulations properly and correctly to maintain desired services. 11 districts in Jambi province, Jambi City government and Tebo district government. Fluctations occur. The difference in regional income between the Jambi city government and Tebo district government is the highest and lowest in 2022. This research aims to determine the comparison of the financial performance of the Jambi City Government and the Tebo Regency Government. 2018- 2022. This research is descriptive quantitative research. Data collection techniques in this research use documentation. The data analysis technique used is descriptive analysis with the formula: Regional Financial Independence Ratio, Effectiveness Ratio, Efficiency Ratio, Harmony Ratio and Growth Ratio. The results of the research show that the financial performance of the Jambi City government and the Tebo Regency government in 2018-2022 seen from the regional financial independence ratio shows that the level of financial independence of Jambi City is on average higher than that of Tebo Regency, seen from the effectiveness ratio shows that the level of effectiveness shows that the government Tebo Regency is more effective than Jambi City, judging from the Efficiency Ratio, it shows that the percentage of Tebo Regency's efficiency level is smaller than Jambi City. Tebo Regency and Jambi City are categorized as less efficient in managing finances, seen from the harmony ratio, it shows that the two regions allocate more funds for operational expenditure than capital expenditure, and seen from the growth ratio, Jambi City's PAD growth is higher than that of Tebo Regency.